Projected irrigation demand for large-scale rice granary under future climate scenarios based on CMIP6 multi-GCM ensemble: a case study of kerian Irrigation Scheme, Malaysia - Mohd Nasir, Muhammad Adib; Harun, Sobri; Zainuddin, Zaitul Marlizawati; Kamal, Md Rowshon (Springer, 2024)
Future climate prediction at a local scale is one of the pressing challenges affecting water management-related mitigation plans. The rice irrigation demands are always related to the climate of the area. This study presents possible changes in the monthly rice irrigation demand patterns under future climate scenarios in the Kerian Irrigation Scheme, Malaysia. An ensemble of five Global Climate Models under three Shared Socioeconomic Pathways (SSPs) (SSP1-2.6, SSP2-4.5, and SSP5-8.5) was employed to help project irrigation demand from 2021 to 2080. The study compared the future projections with the baseline period (1985–2014) and revealed that future irrigation demand changes for two planting periods range between − 1.0 to 0.1% and − 5.3 to − 2.6% during the dry season (February–July) and wet season (August–January), respectively. A significant decrease in irrigation water demand was predicted in September and October for each SSP scenario due to increased rainfall during the wet season, with SSP5-8.5 being the most prominent. Although the temperature and reference evapotranspiratopn (ETo) were predicted to increase, mainly during the near future (2021–2050) rather than the far future (2051–2080), the increase in predicted monthly rainfall successfully copes with the risk of the possible high demand for irrigation supply. Climate change potentially alters the future monthly irrigation water demand pattern, resulting in challenges to water resource management. Predicting the impacts of rice irrigation water demand under the potential future climate change is crucial for Bukit Merah Reservoir to help establish appropriate operational policies for irrigation release for its sustainability.